Profilaxis de enfermedad tromboembólica venosa en pacientes neuroquirúrgicos: A call to action! - Lucía Gómez Suárez; José Antonio Díaz Peromingo (Sociedade Galega de Medicina Interna, 2024)
Prophylaxis for thromboembolic disease in neurosurgical patients